Bio-Mechatronics Development of Robotic Exoskeleton System With Mobile-Prismatic Joint Mechanism for Passive Hand Wearable-Rehabilitation - Vargas, Mariela; Mayorga, J.; Oscco, B.; Cuyotupac, V.; Nacarino, A.; Allcca, D.; Gamarra-Vásquez, L.; Tejada-Marroquin, G.; Reategui, M.; Maldonado-Gómez, R. R.; Vasquez, Y.; de la Barra, Daira; Tapia-Yanayaco, P.; Charapaqui, Sandra; V. Rivera, Milton; Palomares, R.; Ramirez-Chipana, M.; Cornejo, Jorge; Cornejo, José; De La Cruz-Vargas, Jhony A. (Emerging Science Journal, 2024)
The World Health Organization (WHO) estimates that 15 million people are affected by stroke each year, causing deterioration of the upper limb, which is reflected in 70-80% of them, decreasing the performance of daily activities and quality of life, mainly affecting hand functions. Thus, the purpose of this study is to present a high-quality alternative to recover muscle tone and mobility, consisting of a hand-exoskeleton for passive rehabilitation. It covers a motion protocol for each finger and pressure sensors to give a safety pressure range during the gripping function. The bio-design method covers standards (ISO 13485 and VDI 2206) based on biomechanic and anthropometric fundamentals, where Fusion 360 was used for mechanical development and electrical-electronic circuit schematics. The prototyping process was based on 3D printing using polylactic acid (PLA); also, the actuators were servomotors DS3218, the pressure sensors were RP-C7.6-LT, and the microcontroller was Arduino Nano. The system has been validated by the Institute of Research in Biomedical Sciences (INICIB) at the Ricardo Palma University, where the novelty of this work lies in the introduction of a new mobile-prismatic joint mechanism. In conclusion, favorable results were achieved regarding the complete flexion and extension of the fingers (91.6% acceptance rate, tested in 100 subjects), so the next step proposes that the wearable device will be used in the Physical Medicine and Rehabilitation Departments of Medical Centers. Doi: 10.28991/ESJ-2024-08-06-02 Full Text: PDF